In India, diabetes mellitus is on the rise at an alarming rate: A review - Bagchi, Arnab; Pal, Prosanta (Creative Pharma Assent, 2021)
The aim of the current review is to acquaint all the covering aspect of dibetes mellitus which can provide awareness to the diabetes patients in india as well as all over the world. The number of diabetic patients in india is increasing at an alarming rate and is therefore a major area for concern. As per the WHO, the diabetes is expected to reach 79.4 million by 2030. The studies have shown that the type II diabetes is 4-6 times higher in urban than in rural areas in india. Development of diabetes among indians is due to several factors such as age ( Based on NHANES data),waist circumference, hypertention, BMI, smoking habit and total cholestero these variables are important for comparing diabetic and non-diabetic patients